Relationship Between Facilities And Infrastructure On Visitor Satisfaction In Bogor Botanical Gardens - Fransisca Givanya Pamela; Tiara Ayu Utami; Charles Parnauli Saragi (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
The current development of tourism has entered a time when everyone needs tourism to increase creativity, eliminate boredom while working, finding calm, finding local products while traveling, doing business in the scope of tourism, studying the history and culture and language of cultural tribes in Indonesia and foreign countries. Indonesia is a country in the Southeast Asian region, has quite a lot of natural tourism potential and is an attraction for visitors from foreign countries. Bogor Botanical Garden is one of the natural attractions located in the city of Bogor with various types of rare & quite old plants when remembering the age at the first preservation in the Bogor Botanical Gardens. However, the management of the Bogor Botanical Gardens, which is currently under the Indonesian National Research & Innovation Agency (BRIN), is still minimal tourism facilities provided for visitors. This is the background of this research to analyze the relationship between facilities and infrastructure and visitor satisfaction in the Bogor City Botanical Gardens. The research method uses a quantitative approach with a simple linear regression analysis tool. The sampling technique used is nonprobability sampling with purposive sampling technique by taking as many as 100 respondents. The results showed that the variable facilities and infrastructure affect visitor satisfaction, which illustrates that suggestions and infrastructure have a role in visitor satisfaction so that if the manager improves facilities and infrastructure, the satisfaction of visiting will increase. Based on the results of the determination coefficient test, the results of the facility on visitor satisfaction were 72.3% and the remaining 27.7% was influenced by other factors that were not examined in this study. Keyword: Facilities and Infrastructure, Customer Satisfaction, Nature Tourism, Tourism